Scrotoplasty at Time of Penile Implant is at High Risk for Dehiscence in Diabetics. Issue 4 (6th March 2019) - Gupta, Nikhil K.; Sulaver, Randy; Welliver, Charles; Kottwitz, Michael; Frederick, Luke; Dynda, Danuta; Köhler, Tobias S.
ABSTRACT: Introduction: Scrotoplasty has become a common practice during insertion of penile prosthesis, improving patient perception of penile length. Previous reports on scrotoplasty outcomes have only focused on the perceived benefits. The risk of wound complications after scrotoplasty is unknown. Aim: Identify wound complications and associated risk factors of scrotoplasty with insertion of penile prosthesis. Methods: A retrospective review of a single-surgeon series (T.S.K.) of patients who underwent scrotoplasty with initial insertion of inflatable penile prosthesis (IPP) was performed from 2009–2014. Surgical outcomes and wound complications after scrotoplasty were examined, along with patient information, including basic demographics, medical comorbidities, and perioperative data. Main Outcome Measures: Studied outcomes included rate of wound complications after scrotoplasty and IPP insertion and identification of risk factors for wound dehiscence. Results: Of the 103 scrotoplasties performed during the study period, a total of 15 had mild, moderate, or major wound dehiscence. Of these 15 cases, 9 had mild dehiscence and 5 cases had moderate dehiscence and required stitches to be placed in clinic to reinforce the closure. 1 patient had a major dehiscence requiring a return to the operating room for a washout, with exchange of IPP to malleable prosthesis. Multiple risk factors for wound dehiscence were found, including diabetes (odds ratio 6.1, CI 1.5, 25.0, P  = .0129) and scrotoplasty technique (odds ratio 4.9, CI 1.2, 8.6, P  = .003). Other examined variables, including patient age, Peyronie's disease, hypertension, intraoperative penile modeling, smoking, and device manufacturer, were not associated with wound dehiscence. Clinical Implications: Patients with diabetes and scrotoplasties performed via V-Y plasty are more likely to experience wound dehiscence. Strengths & Limitations: Strengths include a single surgeon, thus lending continuity of skill and technique, a consecutive series, and 100% short-term follow-up. Limitations include retrospective design, single institution series, and lack of long-term follow-up. Conclusion: Although scrotoplasty can improve patient satisfaction with IPP, scrotoplasty can lead to increased patient morbidity. Diabetic patients are at increased risk for wound complication after scrotoplasty.